Exploring Current and Future Roles of Non‐Dental Professionals: Implications for Dental Hygiene Education. Issue 9 (1st September 2017) - Maxey, Hannah L.; Farrell, Christine; Gwozdek, Anne
Abstract : The health care system is undergoing transformation in which oral health is not only valued as an aspect of overall health, but health care delivery systems are aligning to better deliver total patient care. As a result of this transformation, education for many non‐dental professionals incorporates oral health content to prepare them to practice in comprehensive delivery models. While some non‐dental professionals already incorporate oral health care in their service, many opportunities exist for expansion of oral health care delivery by other non‐dental professionals, including radiologic technicians, nursing staff, and human services professionals. As non‐dental professionals take on expanded roles in oral health care, the dental hygiene workforce must be prepared to practice in settings with new types of professionals. Dental hygiene curricula should prioritize interprofessional education to best prepare these students for practice in evolved delivery models. This article was written as part of the project "Advancing Dental Education in the 21 st Century."